Preoperative anemia is associated with adverse outcome in patients with urothelial carcinoma of the bladder following radical cystectomy - Gierth, M.; Mayr, R.; Aziz, A.; Krieger, Stefan; Wullich, Bernd; Pycha, A.; Lodde, Michele; Salvadori, U.; Bruendl, J.; Fritsche, H. M.; Hofstaedter, F.; Pawlik, M. T.; et al. (Journal of Cancer Research and Clinical Oncology, 2015)
Radical cystectomy (RC) can be associated with significant blood loss, whereas many patients are presenting with anemia preoperatively. To date, there is a lack of data addressing the impact of preoperative anemia (PA) on survival of patients undergoing RC for urothelial carcinoma of the bladder (UCB).This retrospective multicenter study includes 684 patients with UCB undergoing RC with pelvic lymph node dissection. The median follow-up was 50 (IQR 29,78) months. Anemia was defined in line with the WHO classification (hemoglobin (Hb): male <=13 g/dL, female <=12 g/dL) and based on contemporary gender- and age-adjusted classification (Hb: white male aged <60 years: <=13.7 g/dL; >=60 years: <=13.2 g/dL; white female of all ages <=12.2 g/dL). Univariable and multivariable Cox regression analyses were used to assess the effects of PA on oncological outcomes.A total of 269 (39.3 %) and 302 (44.2 %) patients were anemic according to the WHO classification versus contemporary classification. Age, increased ECOG performance status, advanced tumor stages, lymph node metastasis, positive surgical margin and anemia were associated with disease recurrence (DR), cancer-specific mortality (CSM) and all-cause mortality (ACM). In multivariable analysis, anemia was an independent predictor of DR, CSM and ACM (WHO and/or contemporary classification). Blood transfusion was significantly associated with ACM in both classifications of anemia.PA is significantly associated with worse oncological outcome in patients undergoing RC. Based on the additional unfavorable influence of blood transfusion, this emphasizes the importance of early diagnosis and correction of anemia and implementation of alternative methods of blood volume management.
EVALuna2:16330